Gravitational instability of nearby galaxies: dwarfs vs. spirals - Grebovic, Saladin (My University, 2014)
Star formation is one of the most important subjects in all of astrophysics. Previous analyses have shown that there is a link between star formation and gravitational instabilities in galactic discs. In this thesis we investigate the gravitational instability of 9 dwarf and 12 spiral galaxies from The HI Nearby Galaxy Survey (THINGS), previously analyzed by Leroy et al. (2008), using the Romeo-Falstad (2013) Q stability parameter for multicomponent and realistically thick galactic discs. Our analysis allows us: (1) to quantify how the stability properties of the dwarfs differ from those of the spirals, (2) to determine how the disc stability properties vary with galactocentric distance, and (3) to establish which component dominates the gravitational instability of the disc. We find that the dominant component differs significantly between the two subsamples in a statistical sense. Even so, the median value of the Q stability parameter is nearly independent of galactocentric distance with a value of order unity for both the dwarfs and the spirals, suggesting that galactic discs may be controlled by self-regulation processes. Two important quantities that enter our stability analysis are the stellar and gaseous velocity dispersions, which we find to have a strong impact on disc instability. In all current stability analyses such quantities are estimated through simple models (e.g. Leroy et al. 2008) since they are difficult to measure. However, our analysis illustrates that using observed stellar and gaseous velocity dispersions would be very useful for understanding the complex link between star formation and gravitational instabilities in disc galaxies.
Keywords: Galaktisk astronomi; Informations- och kommunikationsteknik; Galactical astronomy; Information & Communication Technology